Subsidizing compliance: a multi-unit price list mechanism for legal fishing nets at Lake Victoria - Diekert, Florian; Eymess, Tillmann; Goeschl, Timo; Gomez, Santiago; Luomba, Joseph (AWI discussion paper series, 2022)
Like many common-pool resources, the Lake Victoria fisheries are characterized by poor compliance with production input regulations that are intended to reduce overexploitation. To explore the use of input subsidies to increase compliance, we determine the subsidy level required to induce demand for legal fishing nets, thereby 15 compensating fishermen for loss of productivity net of enforcement risk. Our study additionally tests the subsidy-enhancing effect of a norm-nudge. A new multiple price list mechanism for eliciting revealed willingness to pay for multiple units of a production input is developed, adapted to the demands of a challenging field setting, and implemented with 462 fishermen at 20 landings sites on the Tanzanian 20 lakeshore. Consistent with the high prevalence of illegal fishing gear at our sites, we find a zero median demand for legal net panels at local market prices. The subsidy required to shift median demand to at least one legal net panel is a 21% discount. Norm-nudging generates no policy-relevant enhancement of the subsidy.
Keywords: Graue Literatur